Study of Some Serological Tests on Patients with Visceral Leishmaniasis - Salim Musa, Israa (Iraqi Journal of Science, 2023)
This study aimed to measure the alterations in serum zinc (Zn) and acute phaseproteins ( C-reactive protein and Ceruloplasmin) concentrations in patients withvisceral leishmaniasis (VL). A total of 62 individuals were enrolled in this study :52 individuals were infected with visceral leishmaniasis and 10 individuals ashealthy control. Serum zinc levels were significantly (p<0.05) decreased in patientgroup(76.25 ± 4.59 μg/dl ) when compared with healthy control (103.75 ± 3.77μg/dl ) . C-reactive protein , as a mediator of innate immunity, removed damagedcells by activating the classical complement pathway revealed elevated levels inpatients (4.36± 0.23mg/l ) when compared with the healthy control (2.50 ± 0.28mg/l). The level of Ceruloplasmin was also significantly (p<0.05) increased in VLpatients (0.82±0.05 mg/dl) as compred with healthy subjects (0.43±0.03mg/dl).These results showed that serum essential trace elements Zn, C-reactive proteinand ceruloplasmin concentrations have been changed in VL patients. This may bea part of defense strategies of organism.